Analysis Of Public Opinion On Tourist Visit Rates During Covid-19 (Case Study Of Namalatu Beach Tourism And Hunimua Beach Tourism) - Rahmadi Bandjar; A. M. Sahusilawane; Y. M. T. N. Apituley (Utan Kayu Publishing, 2024)
The research aims to determine public opinion regarding the level of tourist visits in the case study of Namalatu beach tourism and Hunimua beach tourism during Covid-19. Respondent sampling was carried out using the purposive sampling method using qualitative analysis. These results show that the level of tourist visits explained during the Covid-19 period was usually mostly local tourists, visits to tourist locations at that time were in accordance with Health protocols and limited visitors came. The number of tourist visits during the Covid-19 pandemic decreased drastically as a result of restrictive government regulations and public concerns about the Covid-19 pandemic. Local tourist visits have also influenced the number of visits to tourist attractions. This shows that the significant decrease in the number of visitors will have a direct effect on the income of small traders in beach tourism. Because traders' income really depends on the number of visitors who visit Hunimua beach and Namaltu beach